The impact of rural loudspeaker systems on typhoon disasters: Guangdong Province of China - Song, Ying Ying; Li, Chao (Frontiers in Earth Science, 2024)
Rural Loudspeaker Systems (RLS) are interrelated with the management of typhoons in Guangdong Province, China. The study aims to determine the effectiveness of RLS devices in reducing injuries, fatalities, and house damage caused by typhoons. Additionally, it examines the role of Typhoon Warning Signals (TWS) level, which can indicate the severity of typhoon that people are alerted about, in conveying typhoon intensity and their impact on disaster outcomes. The analysis used multiple datasets, including RLS coverage, TWS-level, and typhoon disaster records. Poisson regression models are used to estimate the impact of RLS coverage on injuries, fatalities, and house damage. The results reveals that an increase in RLS coverage by one percentage point is associated with an 3% reduction in injury events and an 1% reduction in casualty (injury and fatality) events, highlighting the importance of the RLS as a dissemination tool to inform individuals and guide their behavior during typhoon events. However, house damage, a fixed asset, is not significantly influenced by RLS coverage but is more affected by the severity of the typhoon or TWS-level. These findings enhance the understanding of the influence of RLS devices on mitigating typhoon disasters and underscore the crucial need for implementing effective early warning systems in areas prone to vulnerabilities.